Corn seed industries of Central America and Mexico: relationship between the private and official sectors. - López, Michael (2016)
The partial results of a project from CYMMIT are presented in this article, whose objective is to determine the effects of the agricultural reforms of the corn seed industries in the developing countries, specially the role of the private and official sectors in the production of varieties and hybrids and the release of improved seeds. The analysis is based mainly on asurvey of the seed industries, conducted during 1993 and 1994. The results of the analysis of the total sale of improved seed in 1993, prices according to type and seed origin and the participation of the public and private sectors in developingimproved seed in the Central American countries and Mexico are shown here. The main result from the analysis is that the official sectors are withdrawing from the production and sale of seed, and aiming their efforts to wards breeding and germplasm development. Likewise, the private sectors are important factors of the seed production and sale. The private sector depends on the official materials for their seed sales, specially the small locally financed enterprises and cooperatives of seed producers, as well as Non-Governmental Organizations (NGO's).